EFFECT OF Bifidobacterium animalis ON MICE INFECTED WITH Strongyloides venezuelensis - Goulart Oliveira-Sequeira, Teresa Cristina [UNESP]; David, Erica Boarato [UNESP]; Ribeiro, Claudia [UNESP]; Guimaraes, Semiramis [UNESP]; Batista Masseno, Ana Paula [UNESP]; Katagiri, Satie [UNESP]; Sequeira, Julio Lopes [UNESP] (Inst Medicina Tropical São Paulo, 2014)
The administration of viable Bifidobacterium animalis was tested to induce resistance against Strongyloides venezuelensis infection in mice. Effects on parasite burden, worm length, egg output, and intestinal mucosal histology were evaluated. The oral administration of B. animalis, strain 04450B, starting 14 days before the inoculation of nematode larvae significantly decreased the worm burden and egg output. In probiotic treated animals, the percent reduction of adult worms in the intestine was of 33% and the reduction of egg production was of 21%, compared with those of the control group. The duodenum villous height and villous/crypt ratio were significantly higher in probiotic-treated mice, indicating that this group could be experiencing less intestinal damage. The present findings revealed that the administration of B. animalis for the amelioration of host response to nematode infections is biologically plausible and could have some potential for impacting public health. Meanwhile, further study is needed to delineate the nature and identity of the factor(s) involved in these beneficial effects.
Keywords: Strongyloides venezuelensis; Bifidobacterium animalis; Probiotics; Mice